The application of “S.I.S” technique improves long‐term continence after robotic radical prostatectomy - Song, Qi‐Xiang; Li, Jiayi; Shen, Kai; Peng, Zehong; Qiu, Xudong; Zhu, Hanjing; Gu, Yiyuan; Xu, Wenxin; Wang, Jieying; Zhu, Yinjie; Pan, Jiahua; Dong, Baijun; et al. (Neurourology and urodynamics, 2023)
Aims To propose a novel S.I.S technique during the robotic‐assisted radical prostatectomy (RARP), encompassing pubourethral suspension, posterior wall intensification, and bladder neck stripping, and to present functional and oncological outcomes with a special focus on long‐term continence. Methods From January 1, 2018, to December 31, 2019, consecutive patients who underwent RARP were retrospectively investigated and separated into the S.I.S group and the conventional group. Preoperative patient characteristics, tumor status, and perioperative parameters were collected, followed by the assessment of self‐reported status on continence, using an International Consultation on Incontinence Modular Questionnaire—urinary incontinence short form (ICIQ‐UI‐SF). Statistical comparisons were performed on variables between the two surgery groups, and multivariate logistic regression analysis was used to determine predictive factors for postoperative incontinence severity. Results A total of 602 subjects were analyzed with a median follow‐up of 24 months. There was no significant difference regarding baseline characteristics and perioperative parameters, except for a more advanced tumor stage in the S.I.S group. The application of the S.I.S technique did not jeopardize the positive surgical margin rate at the bladder neck or long‐term tumor control. Notably, the patient‐reported degree of incontinence was significantly reduced with the assistance of S.I.S technique, as evidenced by the diminished severe‐to‐very severe cases. On multivariate analysis, both preoperative body mass index and use of S.I.S modification were independent predictive factors for the long‐term incontinence severity. Conclusions The application of S.I.S technique during RARP is feasible and superior compare with the conventional approach, with a significantly alleviated long‐term incontinence severity, without compromising cancer control.